Pengaruh Faktor-Faktor Ekonomi Makro terhadap Jakarta Islamic Index (JII) Periode 2010-2019 - Zulkarnain, Azim; HS, Sufyati (DINASTI RESEARCH, 2024)
This study aims to determine and analyze the influence of macroeconomic factors such as Gross Domestic Product (GDP), Inflation Rate, SBI Interest Rate, Rupiah / US Dollar exchange rate on the JII (Jakarta Islamic Index) Stock Price Index on the Indonesia Stock Exchange for the period 2010-2019. This study uses an associative quantitative approach which is intended to examine the relationship and influence between macroeconomic factors variables on the JII stock price index variable. Meanwhile, the analysis method used is multiple linear regression. The results of this study indicate that only the rupiah/US dollar exchange rate has a significant negative effect on the JII stock price index. While macroeconomic factors such as Gross Domestic Product, Inflation Rate, SBI Interest Rate have no significant effect on the JII stock price index.